13x-7=11x+3

Simple and best practice solution for 13x-7=11x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13x-7=11x+3 equation:


Simplifying
13x + -7 = 11x + 3

Reorder the terms:
-7 + 13x = 11x + 3

Reorder the terms:
-7 + 13x = 3 + 11x

Solving
-7 + 13x = 3 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
-7 + 13x + -11x = 3 + 11x + -11x

Combine like terms: 13x + -11x = 2x
-7 + 2x = 3 + 11x + -11x

Combine like terms: 11x + -11x = 0
-7 + 2x = 3 + 0
-7 + 2x = 3

Add '7' to each side of the equation.
-7 + 7 + 2x = 3 + 7

Combine like terms: -7 + 7 = 0
0 + 2x = 3 + 7
2x = 3 + 7

Combine like terms: 3 + 7 = 10
2x = 10

Divide each side by '2'.
x = 5

Simplifying
x = 5

See similar equations:

| 3(v-5)=9 | | Y-17=-28 | | 12+5x=-2x+61 | | -4r+5r=r | | V-v+4v=4 | | 4/x-3.4=17 | | 4x-9=3forx | | 1/4z=1 | | 3x-4=12-10 | | 15k-14k-1=13 | | 8m+24=-3m+3 | | 25+(x-5)=90 | | 4w-2w=20 | | 9/3-4*5 | | 20m-19m=2 | | 12x+4x=12 | | 2x^3-6x^2-48x-17=0 | | g(2.5)=2(2.5)-3 | | f(x)=2x^3+3x^2-5 | | (15/4)-2 | | 8q+3q-10q=12 | | 3/2(12/1) | | 12c-8=12c+24 | | -(5/4)(3) | | kx+12=3 | | 12s+4s-8s-7s=19 | | 11=-5.3+y | | 7(6+r)=42+7r | | 6z-2z-4z+2z-z=11 | | 8r+4=29r+7 | | Ln(x^2-9)=ln(x-3)+ln(x+3) | | 3k-10=5k-20 |

Equations solver categories